2001
DOI: 10.1001/jama.285.15.1965
|View full text |Cite
|
Sign up to set email alerts
|

Prior Alcohol Consumption and Mortality Following Acute Myocardial Infarction

Abstract: Self-reported moderate alcohol consumption in the year prior to AMI is associated with reduced mortality following infarction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
97
2
5

Year Published

2001
2001
2013
2013

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 154 publications
(107 citation statements)
references
References 38 publications
3
97
2
5
Order By: Relevance
“…33 Excessive alcohol consumption is also related to stroke and cardiovascular diseases, although moderate alcohol intake might be able to reduce the risk of some diseases, including cardiovascular diseases. [34][35][36][37][38] Our observations support generally reducing intake of alcoholic beverages to prevent hyperuricemia. Such findings will have some impact on the public health policy makers and consumers.…”
Section: Methodssupporting
confidence: 70%
“…33 Excessive alcohol consumption is also related to stroke and cardiovascular diseases, although moderate alcohol intake might be able to reduce the risk of some diseases, including cardiovascular diseases. [34][35][36][37][38] Our observations support generally reducing intake of alcoholic beverages to prevent hyperuricemia. Such findings will have some impact on the public health policy makers and consumers.…”
Section: Methodssupporting
confidence: 70%
“…Regarding comorbidities and alcohol consumption, we did not find differences among groups on overall health based on comorbidity scores. Our results are not in agreement with previous investigations [6,13] that found beneficial health effects associated with moderate alcohol consumption, in particular, the findings of Di Castelnuovo et al [6] regarding the inverse association of intake with total mortality. Mukamal et al [13] also found self-reported moderate alcohol consumption in the year before acute myocardial infarction was associated with reduced mortality after infarction.…”
Section: Discussioncontrasting
confidence: 99%
“…Gmel et al [8] also found the curve depicting the consumption relationship with mortality was influenced by a combination of beneficial and harmful effects. Mukamal et al [13], in a study on long-term mortality among early survivors of acute myocardial infarction, found, compared with abstainers, patients who consumed fewer than one drink/day had a lower all-cause mortality rate than those who consumed one or more drinks/day.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mukamal et al [18] in a prospective cohort study in which the main outcome measure was all-cause mortality found self-reported moderate alcohol consumption in the year before acute myocardial infarction was associated with reduced mortality after infarction. As a consequence of these contradictory reports, in the current study, we investigated whether low or moderate alcohol consumption could be associated with beneficial effects in TKA.…”
Section: Introductionmentioning
confidence: 99%